Nonformal Education in Improving Quality of Life of Underprivileged Children - Abdullah Al Mamun; Kh. Atikur Rahman (Journal of Education and Learning (EduLearn), 2013)
This study explores the role of Non-formal Primary Education (NFPE) in improving the quality of the life of underprivileged children in Bangladesh considering their economic, health, environmental issues and life skills. It uses a mixed method approach of research where three NGOs which run NFPE programs were selected purposefully. Data were derived from six NGO officers, nine teachers, ninety students and eighteen guardians by using two sets of questionnaires for NGO officers and teachers, an interview schedule for guardians and 9 focus group discussions with the students. The findings show that there is no income generating program initiated by the organizations for the learners along with education. So, the scope of their income has reduced. But their daily life behavior and skills have improved. Besides, their awareness on health and environmental issues have increased. The findings lead to some recommendations which will give insights to policy makers and professionals engaged in this field.